Martial Arts among the Bangsamoro Muslim: History, Tradition, Culture, and Religion - Umpa, Morad Sabdullah (JPAIR Multidisciplinary Research, 2018)
In Islam, there are four fundamental factors of social development and change – personality, tradition, accident, and people. The Qur’an says: “Verily never will God change the condition of a people until they change it themselves [with their souls]. (Q-13:11). Therefore, the researcher’s aim is assessing the integration of slamic values in the teaching of martial arts in the youth for them be good followers of Islam thru inculcation in their minds and their behavior the real sense of a true Muslim. Essentially, this study is descriptive, which aimed mainly to serve as an exposition on the Religion, Traditional Culture, and History of the Muslims in the Philippines and their implication relevance to martial arts. The various data collected through in-depth study, interview and observation showed that Islam prepares people to be a fruitful citizen in the society. It also aimed for the total development of man not only in the religious aspect. Thus, Martial arts play a vital role in Islam not just as a means of self-defense, but as a system of ethics. Man and fighting are by nature intimately related; in fact, history shows that they are inseparable. Locally, the Bangsamoro has a very rich historical foundation in martial arts that is directly derivable from the roots of Islamic propagation. And as man became civilized, hand-to-hand fighting also became specialized and humanized and, gradually.
Keywords: Martial Arts; History; Tradition; Culture, Religion; Total development of man; Morality